A 3′ tRNA‐derived fragment produced by tRNALeuAAG and tRNALeuTAG is associated with poor prognosis in B‐cell chronic lymphocytic leukemia, independently of classical prognostic factors. (16th March 2021) - Katsaraki, Katerina; Adamopoulos, Panagiotis G.; Papageorgiou, Sotirios G.; Pappa, Vasiliki; Scorilas, Andreas; Kontos, Christos K.
Abstract: Objective: 3′ tRNA‐derived fragments (3′ tRFs) are important epigenetic regulators in normal and pathological conditions. In this study, we aimed to explore the potential value of a 3′ tRF as a prognostic and/or screening biomarker for B‐cell chronic lymphocytic leukemia (B‐CLL). Methods: Publicly available next‐generation sequencing data from 20 B‐CLL cases were analyzed, followed by prediction of targets of the most abundantly and ubiquitously expressed 3′ tRFs, leading to selection of tRF‐Leu AAG/TAG . PBMCs were isolated from blood samples of 91 B‐CLL patients and 43 non‐leukemic donors, followed by total RNA extraction, in‐vitro polyadenylation, and first‐strand cDNA synthesis. Next, a real‐time quantitative PCR (qPCR) assay was developed for the accurate quantification of tRF‐Leu AAG/TAG and applied in all samples, prior to biostatistical analysis. Results: High tRF‐Leu AAG/TAG levels are associated with inferior overall survival (OS) of B‐CLL patients. The unfavorable significance of tRF‐Leu AAG/TAG was independent of established prognostic factors in B‐CLL. Stratified Kaplan‐Meier OS analysis uncovered the unfavorable prognostic role of high tRF‐Leu AAG/TAG levels for patients in Binet A or Rai I stage, negative CD38 expression, mutated, or unmutated IGHV genomic locus. Conclusion: Our approach revealed the independent prognostic value of a particular 3′ tRF, derived from tRNA LeuAAG and tRNA LeuTAG (tRF‐Leu AAG/TAG ) in B‐CLL.